If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -3x + 2 = x + -2 + 4 Reorder the terms: 2 + 8x + -3x = x + -2 + 4 Combine like terms: 8x + -3x = 5x 2 + 5x = x + -2 + 4 Reorder the terms: 2 + 5x = -2 + 4 + x Combine like terms: -2 + 4 = 2 2 + 5x = 2 + x Add '-2' to each side of the equation. 2 + -2 + 5x = 2 + -2 + x Combine like terms: 2 + -2 = 0 0 + 5x = 2 + -2 + x 5x = 2 + -2 + x Combine like terms: 2 + -2 = 0 5x = 0 + x 5x = x Solving 5x = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 5x + -1x = x + -1x Combine like terms: 5x + -1x = 4x 4x = x + -1x Combine like terms: x + -1x = 0 4x = 0 Divide each side by '4'. x = 0 Simplifying x = 0
| -4e=-28 | | 6w-15=2(3w-5)-5 | | -6(6x+8)=168 | | h(t)=-10t^2+50t | | 6xy=z | | 725=475+25h | | 5(r-6)=23r | | 9x-3(7+2x)=-12 | | (2+7)+5= | | 9x+7=3x+17 | | -7x-12x+81=x+2x-27 | | 1.2w+1.97=0.43 | | 4(-10-5x)=-280 | | 3x+2x+3=45 | | 15y=3y+6y-2 | | 4(2d+4)=48 | | 7y=25 | | (3y)=3 | | 5m=7m-36 | | 5j-3j=4j-24 | | X+9=-3X-7 | | (y^2-7)(9y^2-2y+6)= | | x+270-3x=210 | | 1/6(a-4)=1/2(2a+4) | | 19.03=m-16.27132 | | -3(2x-3)=7(6x+6) | | 4x+9=5x-5 | | x/9+4=2x/5+3 | | -9=-3(7r-5)-2(1-5r) | | 15a-10=-55 | | -4(5m+3)+4=-108 | | 7p+2q=10 |